Impact of transcatheter aortic valve implantation on left ventricular function recovery, mass regression and outcome in patients with aortic stenosis: protocol of the TAVI-NOR prospective study - Sahrai Saeed; Svein Rotevatn; Abukar Mohamed Ali; Daanyaal Wasim; Kjetil Halvorsen Løland; Øyvind Bleie (BMJ Open)
Introduction Transcatheter aortic valve implantation (TAVI) is a widely used treatment option as an alternative to surgical aortic valve replacement in patients with severe aortic stenosis (AS) at high or intermediate surgical risk. TAVI improves symptoms, induces reverse left ventricular (LV) remodelling and increases overall survival. However, a careful patient selection is essential to achieve better outcome. Evidence on LV functional recovery and LV mass regression after TAVI based on contemporary registry data is scarce. The impact of TAVI on the arterial vasculature is also less explored.Method and analyses This is a study of 600 consecutive patients with AS who underwent a TAVI at Haukeland University Hospital, Bergen, Norway. Demographics, clinical data, arterial haemodynamics and echocardiographic parameters were prospectively collected. In the present paper, we describe the design, major scientific objectives and echocardiography imaging protocol of the TAVI-NOR (TAVI in western NORway) study. The main objectives are: To explore the impact of TAVI on cardiac structure and function in patients with severe AS, identify the echocardiographic predictors of reverse LV remodelling, assess survival benefits according to baseline risk profile, evaluate long-term therapeutic success as reflected by reduction in valvular-arterial impedance and to investigate the impact of various types of blood pressure response immediately after TAVI on clinical outcome.Ethics and dissemination The study was approved by the Regional Committees forMedical and Health Research Ethics (REK vest, ref. number 33814) and theInstitutional Data Protection Services. Patients’ consent was waived. The study findings will be disseminated via peer-reviewed publications and presentation in national and international scientific meetings and conferences.Trail registration number The study was registered in the international database: ClinicalTrials.gov, Identifier: NCT04417829.